High Sclerotinia sclerotiorum resistance in rapeseed plant has been achieved by OsPGIP6 - Yin, Meng; Wang, Rui; Li, Shi; Luo, Mei; Wei, Wei; Wang, Maolin; Jiang, Jun; Lin, Yongjun; Zhao, Yun (Frontiers in Plant Science, 2022)
Sclerotinia sclerotiorum, a worldwide distributed fungal pathogen, causes serious adverse effect on the yield and seed quality of rapeseed. Polygalacturonase-inhibiting proteins (PGIPs) can protect the cell wall from degradation by pathogen-secreted polygalacturonases (PGs). The present study found several PGIPs from Oryza sativa, especially OsPGIP6 and 3 have much higher inhibitory activities to SsPGs than BnPGIP2 from Brassica napus. Among them, OsPGIP1, 4, 6 can significantly elevate the resistance of transgenic Arabidopsis to S. sclerotiorum. Subsequently, OsPGIP1, 3, 4, 6 were subjected to SSR resistance assay in transgenic rapeseed plants. Among which, OsPGIP6 showed the highest resistance to S. sclerotiorum. At 48 h after detached leaves inoculation, the lesion area of OE-OsPGIP6 rapeseed plants is only 17.93% of non-transgenic line, and 22.17%, 21.32%, 52.78%, 56.47%, compared to OE-BnPGIP2, OE-OsPGIP1, OE-OsPGIP2, OE-OsPGIP4, respectively. Furthermore, the lesion area of OE-OsPGIP6 reached 10.11% compared to WT at 72 hpi. Also, the lesion length on stem of OE-OsPGIP6 plants was reduced by 36.83% compared to WT. These results reveal that OsPGIP family, especially OsPGIP6, has a great potential in rapeseed S. sclerotiorum-resistance breeding.